Digital Communication as a Tool to Increase Legal Awareness Among the Community - Humaira, Amy; Fitri, Dwi; Musriana, Nanda; Sari, Cut Mutia; Fitriah, Indah Dwi; Hasanah, Yana Farisyah; Azzahra, Syifa Putri; Tuahdiara, Sawfa; Putra, Febri Rizki (Indonesian Journal of Education and Social Humanities, 2025)
The rapid development of digital information and communication technology has brought fundamental changes in the pattern of community interaction, including in efforts to increase legal awareness. Through social media, digital platforms, and other information technologies, the dissemination of legal information has become faster and wider, allowing the public to be more aware of their rights, obligations, and applicable legal norms. This study aims to examine the strategic role of digital communication as a means to strengthen legal awareness among the public. Using a qualitative approach through literature studies of various scientific journals, the results of the study show that digital technology can be an effective tool in educating the law, encouraging transparency, and strengthening social control over law enforcement officers. However, challenges such as low digital literacy, the spread of hoaxes, and misinformation are still obstacles that need to be overcome. Therefore, synergy is needed between the government, educational institutions, and digital platforms to improve legal literacy and build a responsible social media culture, in order to create a more aware, fair, and just legal environment in the digital era.